2018
DOI: 10.1177/2325967118786941
|View full text |Cite
|
Sign up to set email alerts
|

Return to Play Among Elite Basketball Players After Osteochondral Allograft Transplantation of Full-Thickness Cartilage Lesions

Abstract: Background:Osteochondral allograft transplantation (OCA) is a recognized option for full-thickness articular cartilage defects of the knee, especially in the setting of large lesions or those involving the subchondral bone. Previous heterogenous studies of athletes have shown a 75% to 79% rate of return to play after the procedure.Purpose:To define return-to-play rates in a cohort of elite collegiate and professional basketball players following osteochondral allograft of the knee.Study Design:Case series; Lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
53
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 46 publications
0
53
0
Order By: Relevance
“…Both osteochondral autograft transfer and osteochondral allograft transplantation have produced high rates of long-term graft survival, as well as high degrees of reported patient satisfaction and return-to-play among athletes 26,[33][34][35] . For example, a 2016 systematic review found that ~90% of patients who underwent osteochondral autograft transfer had good or excellent outcomes at up to 10 years after surgery 19 .…”
Section: Current Surgical Strategies Repairing Articular Cartilage Dementioning
confidence: 99%
“…Both osteochondral autograft transfer and osteochondral allograft transplantation have produced high rates of long-term graft survival, as well as high degrees of reported patient satisfaction and return-to-play among athletes 26,[33][34][35] . For example, a 2016 systematic review found that ~90% of patients who underwent osteochondral autograft transfer had good or excellent outcomes at up to 10 years after surgery 19 .…”
Section: Current Surgical Strategies Repairing Articular Cartilage Dementioning
confidence: 99%
“…Multiple studies have demonstrated good long-term results, with improvements in both postoperative pain and function 2 , 10 , 28 and a reported 88% rate of return to sport, 14 , 15 including an 80% rate of return to play in professional and collegiate athletes. 3 Anatomically, medial femoral condyle (MFC) and patellar cartilage lesions are the most commonly encountered. 4 , 27 Although most of the existing outcomes literature has focused on condylar OCA, treatment of patellar lesions with OCA has been reported as well.…”
mentioning
confidence: 99%
“…Williams et al [ 66 ] have treated elite and other high-performance athletes, and Balaz et al [ 4 ] and Krych et al [ 36 ] have reported high proportions returning to high level performance.…”
Section: Evidence: Primary Studiesmentioning
confidence: 99%